2020
DOI: 10.1177/0268355520913389
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the great saphenous vein with F-care versus Closurefast endovenous radiofrequency therapy: Double-blinded prospective study

Abstract: Objectives F-care (endovenous radiofrequency, F Care Systems, Antwerp, Belgium) is a relatively new radiofrequency ablation technique for the treatment of venous insufficiency. There is a lack of published data about F-care in literature. This study aimed to prospectively compare the F-care method with conventional endovenous radiofrequency ablation Closurefast method for the management of incompetent great saphenous veins. Methods Between June 2015 and December 2018, 114 patients with incompetent varicose vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The superficial course of GSV is known to increase the risk of skin burns and skin pigmentation. 4,5 Although the patients in both groups had similar superficial GSV courses in our study, the ClosureFast method resulted in a higher rate of skin pigmentation. Therefore, the major reason for this difference is thought to be the lower heat applied to the tissues (70°C in the F-care method) which was reduced by the clot formation on the tip of the catheter in the distal part of the thigh.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The superficial course of GSV is known to increase the risk of skin burns and skin pigmentation. 4,5 Although the patients in both groups had similar superficial GSV courses in our study, the ClosureFast method resulted in a higher rate of skin pigmentation. Therefore, the major reason for this difference is thought to be the lower heat applied to the tissues (70°C in the F-care method) which was reduced by the clot formation on the tip of the catheter in the distal part of the thigh.…”
Section: Discussionmentioning
confidence: 53%
“…There are only a limited number of studies comparing the ablation success rates of those two endovenous radiofrequency catheters with divergent outcomes. [4][5][6] This study aims to compare the monopolar ablation method with the conventional bipolar segmental endovenous radiofrequency ablation method for the management of incompetent saphenous veins.…”
Section: Introductionmentioning
confidence: 99%
“…The adherence to the vein wall was more frequently encountered with the pullback F-care systems with a smaller treatment tip. 11 Bitargil M et al 9 reported that the 1-year occlusion rate in the F-care and Closurefast group were 71.7% and 90.6%, respectively ( P = .013); Nyamekye IK et al 11 have demonstrated complete great saphenous vein closure was significantly better after Closurefast treatment compared with F-care therapy at 6 months (100% vs 79%, P < .01). Contradicting to the results of prior studies, the current study showed that the 1-year occlusion rate of F-care was 98.4%.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few published studies in the literature regarding the F-care endovenous radiofrequency therapy. 9 In this context, the present study was to describe the experience of the F-care RFA combined with UGFS, supplemented by microphlebectomy of the superficial varicose veins and ligation of pathologic perforators.…”
Section: Introductionmentioning
confidence: 99%
“…The 30-d total occlusion rates in the F-Care and Closurefast groups were 96.2% and 98.1%, respectively ( P = 0.5). The 1-year full occlusion rates in the F-Care and Closurefast groups were 71.7% and 90.6%, respectively ( P = 0.013)[ 45 ]. The 3-RF trial is the first RCT of Venefit, radiofrequency induced thermal therapy (RFITT), and endovenous radiofrequency (EVRF) to compare outcomes of RFA devices.…”
Section: Rfamentioning
confidence: 99%